Quantitative ultrasonography in rheumatoid arthritis: evaluation of inflammation by Doppler technique. Issue 7 (1st July 2001) - Qvistgaard, E; Røgind, H; Torp-Pedersen, S; Terslev, L; Danneskiold-Samsøe, B; Bliddal, H
Abstract : OBJECTIVE: To evaluate ultrasonographic methods, including the Doppler technique, as measures of synovial inflammation in finger joints of patients with rheumatoid arthritis. METHODS: Ultrasonography was performed with a high frequency transducer (13 MHz).  Evaluation of the sonographic data was conducted by two independent observers and included measurement of synovial area and thickness (grey tone ultrasound), vascularisation (power/colour Doppler), and indices of the intra- and extrasynovial arterial flow (spectral Doppler). The flow pattern was estimated by the indices of pulsatility (PI) and resistance (RI). RESULTS: The sonographic measurements of joint space were reproducible with intraobserver, intraclass correlation coefficients (ICC) 0.82–0.97 (p<0.0001) and interobserver ICC 0.81 (p<0.0001). The mean (SD) fraction of the synovium vascularised in the patients was 0.15 (0.15). The synovial blood flow was characterised by a diastolic flow—that is, the flow persisting during the diastole. The mean (SD) PI was 1.92 (1.18) and RI 0.70 (0.13). The estimated vascular fraction correlated with the erythrocyte sedimentation rate (ESR) ( r s =0.53, p=0.03). The relative Pi (rPi), an estimate of an abnormally low resistance to vascularisation, correlated with both ESR ( r s =−0.557, p<0.05) and Health Assessment Questionnaire score ( r s =−0.584, p<0.05). After an injection of contrast Levovist the vascular fraction increased, while no difference in PI and RI was observed. CONCLUSION: Ultrasonography is a reliable tool for estimating the size of the joint space and the synovial activity measured by the degree of vascularisation and pattern of flow. Ultrasonography may be useful in monitoring the synovial inflammation in rheumatoid arthritis.